Alt-Virilities: Masculinism, Rhizomatics, and the Contradictions of the American Alt-Right - Vandiver, Josh (Politics, religion & ideology, 2020)
What is the Alt-Right? As a movement still taking shape ideologically and operationally, the Alt-Right demands a research framework for analyzing both what it believes and how it functions. Adopting a morphological approach to analyzing political ideologies, I advance a new criterion for ideological classification: masculinism. Alt-Right masculinism seeks to define and enforce forms of masculinity as normative and regulative ideals with far-reaching implications for the theoretical sources the movement appropriates, the discourses it articulates, and the organizational and operational modes it adopts. Proposing a Deleuzean approach to analyzing how radical movements operate, I argue the Alt-Right functions as a rhizome. In light of these analyses, contradictions within the Alt-Right come into view: the movement seeks to instantiate patriarchal, hierarchal, and phallocentric masculinities through leaderless, networked, and acentric strategies and practices. I conclude by reflecting on how Alt-Right ideology and practice differ from mainstream rightwing masculine ideals and practices—in nationalism, capitalism, militarism, and evangelicalism—and how the development of the Alt-Right sheds new light on the construction of contemporary political masculinities more broadly.